Size and Age as Determinants of Employment Growth among Manufacturing Firms in Pakistan (The Pakistan Development Review, 2025)
Size-based industrial policy (support for small firms) has long been provided by the government in Pakistan while age-based policy (support for young firms) has become prominent in recent years. Both policies are typically justified by reference to positive effects on labour absorption. Despite their popularity among policymakers, however, the empirical basis for such policies has not been adequately analysed at the national level. We address this issue using data from a large, multisector, random sample of manufacturing firms and find empirical support for size-based policies but not for age-based ones. We also find that sizebased policies appear most relevant for firms with less than fifty workers. JEL Classification: Firm Performance: Size, Diversification and Scope (L25); Industrialisation. Manufacturing and Service Industries. Choice of Technology (O14) Keywords: Firm Size, Firm Age, Employment Growth, Manufacturing; Pakistan, Industrial Policy